Riqueza y abundancia de escarabajos copro-necrófagos (coleoptera: scarabaeidae: scarabaeinae) en diversos tipos de cobertura vegetal del puear, Loja-Ecuador - Armijos Armijos, Claudio Romario (2020)
In Ecuador, approximately 200 species of Scarabaeinae have been described. The richness and abundance of the subfamily Scarabaeinae was studied in four vegetation covers at Parque Universitario de Educación Ambiental y Recreacional (PUEAR, for its acronym in Spanish). Three 200-meter transects and 5 sampling points in each transect were placed. Three sampling periods were conducted using pitfall traps baited with human feces (copro-traps) and decomposing chicken (necro-traps) for the collection of specimens. For the community of Scarabaeidae, measures and indices of richness and abundance were calculated, and differences in composition between vegetation cover were evaluated. The richness of Scarabaeinae was higher in forest plantations, while only one species was found in the anthropogenic paramo. The subfamily Scarabaeinae registered higher abundance in the forest (216 individuals) and lower abundance in the anthropogenic paramo (2 individuals). The composition and structure of the communities of the subfamily Scarabaeinae show differences according to the vegetation cover. The similarity index shows there is an affinity between the natural forest, the forest plantations and the bush, however the paramo is notably different from the other vegetation covers evaluated. The structure, composition and state of conservation of the intervened vegetation covers influence the communities of copro-necrophagous beetles. This study registers differences in richness and abundance between the vegetation covers of the PUEAR. Keywords: copro-necrophagus, vegetation coverage, richness, abundance , PUEAR.